ANALYSIS OF THE MANAGEMENT AND CLINICAL ACTIVITY OF THE ANGIOLOGY AND VASCULAR SURGERY DEPARTMENT OF CHUP DURING THE COVID-19 PANDEMIC, FROM MARCH 1 TO MAY 31, AND LESSONS LEARNED - Machado, Rui (2020)
.